Восстановление зарядов 30 мм патронов после истечения срока хранения - Семешко, В. В.; Щербань, В. В. (НТУ "ХПИ", 2010)
This work provides the researches of 30 mm cartridges with a charge from moderated gunpowder 6/7P-5 BP fl. Requirements to change of the content of volatile materials for restoration (regeneration) of characteristics of charges after the expiration of a warranty period of storage are defined. Technological modes for restoration (regeneration) of characteristics of powder charges are checked up. It is defined a value of correction factor to a burning speed considering porous structure of gunpowder
Keywords: снаряд; порох; давление в стволе; баллистические характеристики; скорость заряда